Corn Husk Fiber-Polyester Composites as Sound Absorber: Nonacoustical and Acoustical Properties - Sari, Nasmi Herlina; Wardana, I. N. G; Irawan, Yudy Surya; Siswanto, Eko (Advances in Acoustics and Vibration, 2017)
This study investigates the acoustical and nonacoustical properties of composites using corn husk fiber (CHF) and unsaturated polyester as the sound-absorbing materials. The influence of the volume fraction of CHF on acoustic performance was experimentally investigated. In addition, the nonacoustical properties, such as air-flow resistivity, porosity, and mechanical properties of composites have been analyzed. The results show that the sound absorptions at low frequencies are determined by the number of lumens in fiber, particularly the absorption coefficient, which increases the amount of fiber. For high-frequency sound, the absorption coefficient is determined by the arrangement of fibers in the composite. An absorption coefficient is close to zero when the fibers are arranged in a conventional pattern; however, when they are arranged in a random pattern, a high absorption coefficient can be obtained. The bond interface between the fiber and resin enhances its mechanical properties, which increases the longevity of the composite panel.